Repair of Topoisomerase I-Mediated DNA Damage - Pommier, Yves (2006)
Topoisomerase I (Top1) is an abundant and essential enzyme. Top1 is the selective target of camptothecins, which are effective anticancer agents. Top1-DNA cleavage complexes can also be trapped by various endogenous and exogenous DNA lesions including mismatches, abasic sites and carcinogenic adducts. Tyrosyl-DNA phosphodiesterase (Tdp1) is one of the repair enzymes for Top1-DNA covalent complexes. Tdp1 forms a multiprotein complex that includes poly(ADP) ribose polymerase (PARP). PARP-deficient cells are hypersensitive to camptothecins and functionally deficient for Tdp1. We will review recent developments in several pathways involved in the repair of Top1 cleavage complexes and the role of Chk1 and Chk2 checkpoint kinases in the cellular responses to Top1 inhibitors. The genes conferring camptothecin hypersensitivity are compiled for humans, budding yeast and fission yeast.